Placental growth factor and placental perfusion - Sara Francesca Deiana; Ileana Atzeni; Alessandra Meloni; Silvia Soddu; Giuseppina Parodo; Melania Puddu; Erica Vannelli; Alessandra Atzei; Gavino Faa; Vassilios Fanos; Gian Benedetto Melis; Anna Maria Paoletti (Hygeia Press di Corridori Marinella, 2014)
Placental Growth Factor (PlGF) is a very important angiogenic protein secreted by the placenta, necessary for the proper functioning of the endothelial cells during pregnancy. In normal pregnancies, PlGF plasma circulating levels increase up to the 32nd week of pregnancy, and then decrease until the end of pregnancy. Low PlGF plasma levels are a marker of preeclampsia and of placental function deficiency. The aim of our study was to evaluate whether a deficiency of placenta function, diagnosed through the PlGF assay, could be a cause of preterm delivery without known causes. The PlGF levels were measured in plasma samples collected by 250 pregnant women (20-35 weeks of pregnancy). In our study, PlGF levels were significantly lower than cut off values in all women with preterm delivery without known causes.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken